Are There Compelling Reasons to Establish a Connection between STEM and STS Education? - Antonio García-Carmona (Trilogía Ciencia Tecnología Sociedad)
This article examines whether there are compelling reasons to establish a relationship between the STEM (Science, Technology, Engineering, and Mathematics) and STS (Science, Technology, and Society) educational movements. To address this issue, the analysis focuses on the origins, objectives, defining characteristics, and specific classroom implementations of each movement. The findings suggest that linking STEM and STS education is a significant challenge, as sufficient and strong arguments are lacking to support such a connection. Each movement emerged from a distinct historical, sociopolitical, and economic context and pursues equally different educational approaches and intentions. The only commonality identified between the two educational movements is that neither has yet succeeded in implementing an authentic and effective integrated education in the classroom, despite what their respective acronyms suggest. However, this does not imply any substantive connection between STS and STEM education; it is merely coincidence.